Engaging Respectfully with Indigenous Knowledges: Copyright, Customary Law, and Cultural Memory Institutions in Canada - Callison, Camille; Ludbrook, Ann; Owen, Victoria; Nayyer, Kim (KULA)

(untitled) (University of Victoria Libraries, 2021)
This paper contributes to building respectful relationships between Indigenous (First Nations, Métis, and Inuit) peoples and Canada's cultural memory institutions, such as libraries, archives and museums, and applies to knowledge repositories that hold tangible and intangible traditional knowledge. The central goal of the paper is to advance understandings to allow cultural memory institutions to respect, affirm, and recognize Indigenous ownership of their traditional and living Indigenous knowledges and to respect the protocols for their use. This paper honours the spirit of reconciliation through the joint authorship of people from Indigenous, immigrant, and Canadian heritages. The authors outline the traditional and living importance of Indigenous knowledges; describe the legal framework in Canada, both as it establishes a system of enforceable copyright and as it recognizes Indigenous rights, self-determination, and the constitutional protections accorded to Indigenous peoples; and recommend an approach for cultural memory institutions to adopt and recognize Indigenous ownership of their knowledges, languages, cultures, and histories by developing protocols with each unique Indigenous nation.